Efforts to Increase Student Activeness Using the TGT (Teams Games Tournament) Learning Method in Hurdle Running Lessons at State Junior High School 8 Banjarbaru - Rizaldi, Muhammad; Rakhman , Arie; Putra, Trinaldi Andika (Empiricism Journal, 2026)
This research was motivated by the low student activeness in Physical Education (PJOK) learning on hurdles material among eighth-grade students of State Junior High School 8 Banjarbaru. This study aimed to improve student activeness through the implementation of the Teams Games Tournament (TGT) cooperative learning model. A Classroom Action Research (CAR) design was employed, conducted collaboratively across two cycles. The subjects were 32 eighth-grade students of State Junior High School 8 Banjarbaru in the even semester of the 2025/2026 academic year. Data were collected through structured observation using student activeness observation sheets (15 indicators, 1–4 scale) and teacher activity observation sheets (21 indicators, 1–4 scale), validated through expert judgement. Comparative descriptive analysis was applied by comparing results across the pre-cycle, Cycle I, and Cycle II. Results showed progressive improvement: student activeness in the Active and Very Active categories increased from 28.13% (pre-cycle) to 62.50% (Cycle I) and 90.63% (Cycle II). In Cycle II, several corrective actions were implemented, including simplification of tournament rules, addition of game variations, intensification of teacher guidance, and provision of more varied rewards. Teacher activity scores also rose from 69.05% to 82.14% and 86.90% respectively, reaching the Very Implemented category. It is concluded that the TGT learning model supported the improvement of student activeness in PJOK hurdle running learning.